Ecto-phosphorylation on aortic endothelial cells. Exquisite sensitivity to staurosporine. - Pirotton, S (1992)
One- and two-dimensional gel electrophoresis of proteins from bovine aortic endothelial cells (BAEC) incubated with [gamma-32P]ATP revealed the preferential labelling of a cell-associated 21 kDa substrate. The labelling of this band was detectable within 30 s, increased up to 30 min and was stable for at least 3 h following the wash-out of the ATP. This protein was also labelled after incubation of the cells with [gamma-35S]ATP. Incorporation of radioactivity into the 21 kDa band did not occur if the endothelial cells were treated with low concentrations of trypsin (0.01%) before or after the labelling period. The pattern of BAEC protein phosphorylation by [gamma-32P]ATP was completely different from that of the fetal calf serum used for the cell culture. The presence of serum during the incubation of BAEC with [gamma-32P]ATP did not modify qualitatively the labelling pattern and, in particular, did not enhance the phosphorylation of the 21 kDa substrate; this suggests that neither the kinase nor the 21 kDa substrate are adsorbed serum proteins. Staurosporine, a protein kinase inhibitor with low specificity, decreased the labelling of the 21 kDa protein with an IC50 of 2 nM. In contrast, at 100 nM, staurosporine did not decrease the accumulation of inositol phosphates induced by ATP via the activation of P2y receptors. These data indicate the presence of aortic endothelial cells of an ecto-kinase which uses extracellular ATP to produce the selective and long-lived phosphorylation of a 21 kDa endothelial substrate. Ecto-phosphorylation of this protein might play a role in the modulation of endothelial cell functions by ATP, in addition to the P2y receptors [Boeynaems & Pearson (1990) Trends Pharmacol. Sci. 11, 34-37]. The exquisite sensitivity of ecto-phosphorylation to inhibition by staurosporine and its specific inhibition by some isoquinolinesulphonamide compounds provide potential pharmacological tools to investigate this hypothesis.